Sodium nitrite prevents both reductions in circulating nitric oxide and hypertension in 7-day lead-treated rats - Gonçalves-Rizzi, Victor Hugo [UNESP]; Nascimento, Regina Aparecida [UNESP]; Possomato-Vieira, Jose Sergio [UNESP]; Dias-Junior, Carlos A. [UNESP] (Nordic Association for the Publication of BCPT, 2015)
Hypotensive effects of oral sodium nitrite have been reported as alternative sources of nitric oxide (NO) formation in animals and human beings. Reductions in NO bioavailability were observed in lead-induced hypertension. However, no previous study has examined whether a single daily dose of sodium nitrite prevents the reductions in the NO bioavailability in lead-induced hypertension. Then, we expanded previous reports and evaluated the effects of sodium nitrite in 7-day lead-treated rats. Wistar rats were divided into four experimental groups: Pb+sodium nitrite group received intraperitoneally (i.p.) 1st dose 8 µg/100 g of lead acetate and a subsequent dose of 0.1 µg/100 g, and daily treatment with sodium nitrite (45 mg/kg/day) or water (Pb group) by gavage for 7 days; Sodium nitrite group received i.p. 1st dose 8 µg/100 g of sodium acetate and a subsequent dose of 0.1 µg/100 g, and daily treatment with sodium nitrite (45 mg/kg/day) or water (saline group) by gavage for 7 days. Similar and higher whole-blood lead levels (11.5 ± 1.2 and 13.2 ± 0.7 µg/dL) were found in lead-exposed rats treated with either water or sodium nitrite (Pb or Pb+sodium nitrite, respectively; both p  <  0.05 versus control groups). We found lower NO markers such as plasma nitrite and nitrite + nitrate (NOx) levels (both p < 0.05 versus controls) in lead-exposed rats compared with normotensive (sodium acetate)-treated controls (Pb group versus saline group; p  <  0.05). Lead induced increases in systolic blood pressure (from 130 ± 2 to 164 ± 6 mmHg in Pb group; p  <  0.05); however, both lead-induced decreases in NO markers and hypertension (Pb+sodium nitrite group versus Pb group; both p  <  0.05) were prevented by a single daily dose of sodium nitrite. In conclusion, these findings are consistent with the idea that impaired NO bioavailability contributes to the maintenance of elevated blood pressure in lead-induced hypertension. Additionally, our results show that sodium nitrite exerts antihypertensive effects in lead-induced hypertension and provide evidence that sodium nitrite prevents the impairment of NO, thus, reaffirming the relevance of nitrite as alternative source of recycling back to NO.